Investigation of capacitors and electrical circuit elements performance of magnetic biocomposites prepared by using the hemp biomass - Coskun, Ramazan; Yalcin, Orhan; Okutan, Mustafa (ELSEVIER SCIENCE SA, 2023)
Hemp biomass (HB) was brought into activated hemp biomass (AHB) by chemical technique and all samples were obtained by doping different nanoparticles. Structural, dielectric and magnetic characterizations for all samples were performed by using the XRD, FTIR, SEM, EDX, LCR Meter and PPMS at room temperature. The characteristics of both hemp biomass and nanoparticles in the structures of these samples were examined in detail. In addition to HB and AHB samples, the contribution of lignin and pectin characteristic bands to con-ductivity was investigated in AHB samples doped with Fe3O4, MgFe2O4 and SrFe2O4 nanoparticles. It has been determined that homogeneously dispersed nanoparticles contribute to surface area, crystallization and con-ductivity and these samples are technological products. It was determined that the samples could be used as batteries, and two electrical circuits simultaneously connected to the lignin and pectin structures of the activated hemp biomass (AHB) doped with different types of nanoparticles were obtained from the Smith-Chart diagram.
Keywords: Hemp biomass; Dielectric properties; Organic conductivity; Electrochemical biosensor; Smith chart; Capacitor; COMPOSITES; FIBERS; Materials Science